Public relations of Iraqi companies and their role in the marketing of national products - Hammadi, Ahmed Sahi; Al Shafei, Abdul Mohsin (ALBAHITH ALALAMI, 2021)
based on the importance of public relations in companies, I will discussed the issue of public relations and its role in marketing national products, given what these companies represent of great importance in terms of providing products and services to large segments of Iraqi society, which necessitated the need to search and investigate the role and importance of activities that Provides public relations in Iraqi companies in all categories( public, private and mixed). the study tables and theirinterpretations, results and recommendations, and the studyreachedseveralresults, including the positive and the negative, the positive including the success in marketing the products by the number of companies in the Fairswhere the level of participation washigh and a highpercentage and also the greatbenefitachieved by the companies In promotingitsproductsthrough the high and increasingpopularity of the visitors of the Fairs. As for the negativeresults, includingthat the level of demand for the national productwasModerutedcompared to the Arab and international product, dui To the lack of public confidence in the local product and the highquality of the Arab and international product.